2021
DOI: 10.1109/access.2021.3132133
|View full text |Cite
|
Sign up to set email alerts
|

Computer-Aided Ear Diagnosis System Based on CNN-LSTM Hybrid Learning Framework for Video Otoscopy Examination

Abstract: Ear disorders are among the most common diseases treated in primary care, with a high percentage of non-relevant referrals. The conventional diagnostic procedure is done by a visual examination of the ear canal and tympanic membrane. Consequently, the accuracy of the diagnosis is affected by observer-observer variation, depending on the technical skill and experiences of the physician as well as on the subjective bias of the observer. This situation impacts the proper implementation of treatments, increases he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…An extended dataset with diverse disease patterns can be used to validate the generality and robustness of our classification and improve the prediction performance of TM changes. In the same vein, when applied to otoendoscopic video sequences [ 15 ], it can help overcome the bias of still image-based prediction. Cerumen, which was not included in this study, may limit the information on TMs required for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…An extended dataset with diverse disease patterns can be used to validate the generality and robustness of our classification and improve the prediction performance of TM changes. In the same vein, when applied to otoendoscopic video sequences [ 15 ], it can help overcome the bias of still image-based prediction. Cerumen, which was not included in this study, may limit the information on TMs required for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the recording ends once the specula have been removed from the patient's ear producing unnecessary frames. Assuming that the central frame of the video shows the tympanic membrane and (or) the ear canal [8], we calculate the histogram of such a frame and compare it to each of the frames in the video using the Kullback-Leibler divergence score. If the score falls below a certain threshold, the frame is discarded.…”
Section: Image Domain Analysismentioning
confidence: 99%
“…Due to the advent of advanced processing techniques and the large volume of digital data available today, new technology to assist medical diagnosis has been generated as an increasing tendency to reduce diagnostic error in the last few years [6]. Some studies [7][8][9] have demonstrated the benefit of using artificial intelligence (AI) to improve and diagnose safety for ENT pathologies of various types by achieving a diagnostic performance of over 90%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this diagnostic dilemma and improve diagnostic accuracy, several methods, such as decision trees, support vector machines (SVMs), neural networks and Bayesian decision approaches, have been used to train different learning models and predict whether an image corresponds to a normal ear or an otitis media case. 8 , 9 Myburgh et al. utilized a video endoscope to acquire images and a cloud server for pre-processing and entered the images into a smartphone-based neural network program for diagnosis.…”
Section: Introductionmentioning
confidence: 99%